Reaksi Pasar Saham Terhadap Peristiwa Politik di Parlemen Indonesia Tahun 2014 (Studi Peristiwa Pada Perusahaan yang Terdaftar di BEI) - Yovinda Trista Yuliana; I Made Sudana (Forum Manajemen Indonesia (FMI), 2015)
Many political events occur in the parliament over 2014, namely announcement of â€œUU No. 17 Tahun 2014 about MD3â€ on July 8th, â€œRUU Pilkadaâ€ on September 26th, and Peopleâ€™s Representative Council (DPR) election on October 2nd. The events are considered as information that could affect compayâ€™s stock price on Indonesia Stock Exchange, which will be reacted by the investor if the information is relevant. So, the objective of this research is to observe stock market reaction around the announcement date of political event in the parliament of Indonesia. Event study is applied to each announcement, 310 samples for â€œUU No. 17 Tahun 2014 tentang MD3â€, 322 samples for â€œRUU Pilkadaâ€, and 284 samples for Peopleâ€™s Representative Council (DPR) election. Using seven days length for window event period, three days before the event, during the event, and three days after the event. By using one-sample t-test for AAR as measuring indicator, there are significant negative AAR at t+1 of the three events. Meanwhile by using CAAR as an indicator, negative result was significant only at the announcement of â€œUU No. 17 Tahun 2014 about MD3â€, but positive significant on â€œRUU Pilkadaâ€ and Peopleâ€™s Representative Council (DPR) election. Key words: politics, parliament, event study, average abnormal return (AAR), cumulative average abnormal return (CAAR)